CiiEM 2021 - Barroso, Helena; Castro, Cidália (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book brings together works submitted to the 5th International Congress of CiiEM, which were selected for publication, in areas as diverse as Microbiology, Public Health, Forensic Sciences, Psychology, Dentistry, Sociology, Biomaterials, Biology, Nursing, Nutrition Sciences, Pharmaceutical Sciences, Physiotherapy, Psychology, Social Sciences and Medicine. The congress was focused on Reducing Inequalities in Health and Society, and the works gathered here reflect the diversity and interdisciplinarity that characterized this scientific meeting.